Role of son elastography in predicting positive sperm retrieving in patients with azoospermia (Eurasian Medical Research Periodical, 2022)
Infertility is an important community problem & about 10-30 % is due to azoospermia. Many causes of azoospermia were found. It's either obstructive or non-obstructive. When testicular biopsy is negative, this means that it's a non-obstructive azoospermia. When testicular biopsy is positive, this means that it's either an obstructive or a non-obstructive azoospermia